(3QSGdI aj GdaQb Hjf GdaQb GdeNJdaIs - (3GdGeOjs
(3ChdgG (B:s
(3ai PcQ GdaQb GdJi CTGQ EdjgG GdQShd (B" (3U(B" (3Hbhdg SJaQb CeJi KdKoG hSHYjf aQbI s
(3BNQgG (B:s
(3heG jecf Cf jJeSc Hg ai OaYgG ef GdCLhHI faY Gddg Hg GdWGdHjf hGdMeO ddg Ydi GdJGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3hbO CJe GdeDda JCdja gPg GdQSGdI SfI (B907 (3g`s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs